Mindfulness to improve the mental health of university students. A systematic review and meta-analysis - González-Martín, Ana María; Aibar-Almazán, Agustín; Rivas-Campo, Yulieth; Castellote-Caballero, Yolanda; Carcelén-Fraile, María del Carmen (Frontiers in Public Health, 2023)
Objectives This systematic review and meta-analysis was to analyze the effects of a mindfulness program on mental health in university students. Methods A systematic review was conducted using the databases Pubmed, Scopus, Web of Science and CINAHL. The selected studies had to incorporate a mindfulness intervention in university students. The methodological quality of the collected articles was evaluated using the PEDro scale. Results We initially identified 321 studies, of which 21 were included in this review. The interventions focused on mindfulness with durations ranging from 8 weeks to 3 months. The results demonstrated significant effects of a mindfulness intervention on mental health in university students. Conclusion This systematic review and meta-analysis found that mindfulness is effective for improving the mental health of college students. Systematic Review Registration identifier: CRD42023441453.